Foreword - Matthew S. Sachs (Fungal Genetics Reports, 2001)
The 48th edition of the Fungal Genetics Newsletter contains articles and notes on a wide variety of topics. As usual, the Aspergillus and Neurospora bibliographies are included, as is the most recent FGSC mailing list. The abstracts from the Twenty-First Fungal Genetics Conference at Asilomar are published as an electronic supplement available at the FGSC web-site.